The Authority of Translators: Vendors, Manufacturers, and Materiality in the Transfer of Barlaam and Josaphat along the Silk Road. Issue 3 (16th November 2017) - Høgel, Christian
Abstract : Texts–and the stories and teachings they contained–travelled far along the Silk Road in the hands of merchants, missionaries, monastic communities and many more. The intricate itineraries and the many languages and scripts used on the way have received much attention, and we can therefore follow some of the stages and versions that stories like the Barlaam and Josaphat (as it was known in the West) went through in its long journey from Sanskrit India to e.g. Norse-writing Norway. But in studies of such transfer of texts, translation has mainly been seen as a linguistic enterprise, requiring language skills and linguistic strategies of translators. The present paper aims at involving also material aspects of this process, focusing on the material conditions into which texts were inscribed on the way. The transformation from stringed palm leaves, to single parchment leaves or rolls, and then to bound codices also had an impact on the structure, presentation and symbolic value of these texts. Layout, the place and possibility of illuminations, as well as the portability and physical resilience of the written text all depended on the traditional manners of book production, and these varied immensely over the expanse of the Silk Road. Being authoritative to various degrees in themselves, texts entered, when translated and re-circulated, into a universe of multiple authority holders where translators (in a broad sense) would have to reinvent authoritative presentations of the new text, acting in many ways as vendors of it. This would in itself imply a–brief–authoritative position, comparable to the 'authority of the seller' auctoritas venditoris, as expressed in Roman law.